Proton-coupled electron transfer mechanisms of the copper centres of nitrous oxide reductase from Marinobacter hydrocarbonoclasticus – An electrochemical study - Carreira, Cíntia (2022)
PTDC/BBB-BQB/0129/2014, FCT/MCTES, UID/Multi/04378/2019, UID/QUI/50006/2019, Centro de Quimica Estrutural multiannual funding 2020-2023, UID/QUI/00100/2019.